2011
DOI: 10.1074/jbc.m111.241893
|View full text |Cite
|
Sign up to set email alerts
|

TRIM32 Protein Sensitizes Cells to Tumor Necrosis Factor (TNFα)-induced Apoptosis via Its RING Domain-dependent E3 Ligase Activity against X-linked Inhibitor of Apoptosis (XIAP)

Abstract: TRIM32, which belongs to the tripartite motif (TRIM) protein family, has the RING finger, B-box, and coiled-coil domain structures common to this protein family, along with an additional NHL domain at the C terminus. TRIM32 reportedly functions as an E3 ligase for actin, a protein inhibitor of activated STAT y (PIASy), dysbindin, and c-Myc, and it has been associated with diseases such as muscular dystrophy and epithelial carcinogenesis. Here, we identify a new substrate of TRIM32 and propose a mechanism throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 61 publications
5
51
2
Order By: Relevance
“…Consistent with previous findings (Albor et al, 2006;Locke et al, 2009;Ryu et al, 2011), the expressed FLAG-TRIM32 was biologically active and was heavily autoubiquitylated in the cells, as demonstrated by a smear of high-molecular-mass species of HA-ubiquitin (Fig. 4A, lanes 2 and 8).…”
Section: -3-3 Binding Affects the Formation Of Trim32-containing Cbssupporting
confidence: 77%
See 2 more Smart Citations
“…Consistent with previous findings (Albor et al, 2006;Locke et al, 2009;Ryu et al, 2011), the expressed FLAG-TRIM32 was biologically active and was heavily autoubiquitylated in the cells, as demonstrated by a smear of high-molecular-mass species of HA-ubiquitin (Fig. 4A, lanes 2 and 8).…”
Section: -3-3 Binding Affects the Formation Of Trim32-containing Cbssupporting
confidence: 77%
“…The interaction of all these 14-3-3 isoforms with FLAG-TRIM32 were stimulated by coexpression of cPKA in HEK293 cells (Fig. 2C), a cell line widely used in the study of TRIM32 interaction and localization (Kano et al, 2008;Locke et al, 2009;Ryu et al, 2011). Phosphate incorporation into TRIM32 under these conditions was confirmed using phospho-PKA substrate antibodies (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…TRIM32 has been shown to be elevated in epidermal and epithelial tumorigenic cells, where its antiapoptotic and carcinogenic roles have been discovered (19,38,39). However, TRIM32 overexpression/knockdown experiments in established cell culture lines have suggested a proapoptotic, tumor suppressive role for TRIM32 (40). Our data demonstrate that apoptosis is not perturbed in TRIM32-deficient skeletal muscle and that it is not an essential pathogenic feature of Trim32 -/-myopathy.…”
Section: Figurementioning
confidence: 55%
“…Apoptosis contributes to skeletal muscle remodeling to maintain a constant nuclearto-cytoplasm ratio during hind limb suspension or immobilization (37). Moreover, it's been previously shown that TRIM32 may play an antiapoptotic role in epidermal keratinocytes (38) and squamous epithelial cells (39) but a proapoptotic role in some established cell culture lines (40). Therefore, we examined whether apoptosis is altered in skeletal muscle during hind limb suspension/reloading in the absence of TRIM32.…”
Section: Figurementioning
confidence: 99%